Determinants of pharmaceutical innovation: The role of technological opportunities revisited - Bastian Rake (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Recent empirical contributions emphasize the importance of (potential) market size for the development of new pharmaceuticals. At the same time many scholars point out the importance of of scientific advances for the industry's R&D activities. Against this background I analyze the relationship between (potential) market size, technological opportunities, and the number of new pharmaceuticals in the United States. Technological opportunities are operationalized as growth rates of the relevant knowledge stock as proposed by Andersen (1999, 1998). I analyze a unique dataset by using an entry stock Poisson quasi-maximum likelihood estimator. The results reveal a rather robust and significantly positive response of the number of new pharmaceuticals, i.e., new molecular entities or new drug approvals, to market size and technological opportunities.
Keywords: O31; J10; J20; 330; Determinants of Innovation; Pharmaceuticals; Demand; Technological Opportunities; Pharmazeutische Forschung; Produktinnovation; Arzneimittelmarkt; Technischer Fortschritt; USA